The Arabidopsis TNL immune receptor BNT1 localizes to the plastid envelope and mediates flg22-induced resistance against Pseudomonas - Peppino Margutti, Micaela Yesica (2025)
Precise localization and trafficking of plant immune receptors are critical for their function. We identify the TNL-class nucleotide-binding leucine-rich repeat receptor (NLR) BURNOUT1 (BNT1) from Arabidopsis thaliana as localized to plastids, key organelles for plant immunity. Alternative transcription start site usage generates two isoforms of BNT1: BNT1.2, which is targeted to the plastid envelope via an N-terminal signal-anchored mechanism, and BNT1.1, which resides in the cytoplasm. Moreover, BNT1.2 is predominantly expressed in epidermal cells, where it localizes to the so-called sensory plastids. Functional analysis revealed that bnt1 mutants exhibit compromised PAMP-triggered immunity (PTI) responses, including impaired callose deposition and reduced flg22-induced resistance to Pseudomonas syringae pv. tomato, while flg22-induced apoplastic reactive oxygen species production remains unaffected. Notably, only the plastid-localized BNT1.2 isoform is required for these PTI responses. Our findings reveal a role for NLRs in regulating PTI responses from plastids and highlight these organelles as key hubs for signal(s) integration during plant-pathogen interactions.